Solitary colonic metastasis from hepatocellular carcinoma - Zhenxing Zhang; Kewei Ji; Guolin Zhang; Kelong Tao; Guangen Xu; Shan Wang (Medicine, 2026)
Rationale: Hepatocellular carcinoma (HCC) is a malignant tumor with the potential for intrahepatic and extrahepatic metastatic spread. Although extrahepatic metastases commonly involve the lungs, lymph nodes, bones, and adrenal glands, gastrointestinal (GI) metastasis, particularly colonic metastasis, is extremely rare. Due to its low incidence and nonspecific endoscopic manifestations, colonic metastasis from HCC can be easily misdiagnosed as a primary colorectal neoplasm. Herein, we report a rare case of colonic metastasis from HCC detected during long-term postoperative surveillance and highlight the importance of considering atypical metastatic sites in patients with HCC. Patient concerns: A 76-year-old male patient with a history of HCC was found to have a colonic lesion during routine postoperative abdominal computed tomography (CT) surveillance. Seven years earlier, he had been diagnosed with HCC and underwent partial resection of liver segment IV. The patient had evidence of previous hepatitis B virus (HBV) exposure and was receiving oral entecavir therapy. Diagnoses: Contrast-enhanced CT revealed an occupying lesion at the hepatic flexure of the colon. Colonoscopy demonstrated an approximately 4.0-cm elevated lesion with surface congestion and erosion. Biopsy showed necrotic tissue with a small number of atypical cells, initially suggesting metastatic HCC. The patient subsequently underwent right hemicolectomy. Histopathological examination of the resected specimen revealed an elevated tumor in the ascending colon, consistent with metastatic HCC. Immunohistochemical analysis demonstrated positive Hepatocyte expression and negative CK20, CDX2, and Villin expression, supporting hepatic origin and excluding primary colorectal adenocarcinoma. Interventions: The patient underwent right hemicolectomy for the colonic lesion. Postoperative antiviral therapy with entecavir was continued, and regular surveillance was performed. Outcomes: The patient recovered uneventfully after surgery and was discharged on postoperative day 10. At the 2-year follow-up, he remained alive without evidence of recurrent disease or newly identified metastatic lesions. Lessons: Colonic metastasis from HCC is exceptionally rare and may mimic primary colorectal malignancy. The diagnosis requires careful integration of clinical history, pathological morphology, and immunohistochemical findings. Hematogenous dissemination may represent a possible mechanism of colonic involvement. Clinicians should consider gastrointestinal metastasis during long-term surveillance of patients with HCC, especially in regions with a high prevalence of HBV infection.